2019
DOI: 10.3354/meps12907
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of population size of arborescent octocorals on shallow Caribbean reefs

Abstract: The coral reef crisis is defined by declining cover of scleractinians, but on Caribbean reefs it also is associated with increasing abundances of octocorals. The demographic causes of these increases are not understood, but parallels between marine 'forests' of octocorals, and terrestrial forests of trees (e.g. formation of a 3-dimensional framework providing habitat), suggests that insights into causation might be found by comparing the 2 types of forest. This study describes communities of octocorals in St. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 74 publications
2
19
0
Order By: Relevance
“…Addressing mechanisms promoting octocoral success has benefitted from the analogy with terrestrial forests ( Rossi et al, 2017 ), which has motivated consideration of the emergent consequences of dense stands of octocorals. These include creating a unique sub-canopy flow regime ( Guizien & Ghisalberti, 2016 ), modified recruitment ( Privitera-Johnson, Lenz & Edmunds, 2015 ), and a context in which self-thinning (sensu Yoda et al, 1963 ) might play a role in regulating population size ( Edmunds & Lasker, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Addressing mechanisms promoting octocoral success has benefitted from the analogy with terrestrial forests ( Rossi et al, 2017 ), which has motivated consideration of the emergent consequences of dense stands of octocorals. These include creating a unique sub-canopy flow regime ( Guizien & Ghisalberti, 2016 ), modified recruitment ( Privitera-Johnson, Lenz & Edmunds, 2015 ), and a context in which self-thinning (sensu Yoda et al, 1963 ) might play a role in regulating population size ( Edmunds & Lasker, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The shallow reefs on the south shore of St. John, U.S. Virgin Islands, have recently undergone a shift in benthic community structure that favors octocorals 21,22,[41][42][43][44] . The decline in abundance of scleractinians has been recorded in detail [45][46][47] .…”
mentioning
confidence: 99%
“…Evidence of density-dependent effects were not detected in the present study, even though densityassociated recruitment was reported from this locality for G. ventalina over and 2014(Privitera-Johnson, Lenz & Edmunds, 2015, and Eunicea spp. in 3 of 4 years from 2014-2017 (Edmunds & Lasker, 2019), and signs of self-thinning were found for Eunicea spp. in shallow water (9-m depth) adjacent to Tektite (Edmunds & Lasker, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Addressing mechanisms promoting octocoral success has benefitted from the analogy with terrestrial forests (Rossi et al, 2017), which has motivated consideration of the emergent consequences of dense stands of octocorals. These include creating a unique sub-canopy flow regime (Guizien & Ghisalberti, 2016), modified recruitment (Privitera-Johnson, , and a context in which self-thinning (sensu Yoda et al, 1963) might play a role in regulating population size (Edmunds & Lasker, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation